Analisis Kemampuan Membaca dan Menulis Al-Qur’an Siswa Kelas V-E di Sekolah MIN 12 Medan Tembung: Analysis Of The Ability To Read And Write The Qur'an For V-E Class Students At MIN 12 Medan Tembung School - Arlina; Djodi Priantono; Ismail Effendi Nasution; Raudhatul Munawwarah; Yulia Haliza Lubis (STAI DDI Makassar, 2022)
Learning and teaching reading and writing the Koran in the right way so that it is in accordance with makhraj and tajwid is an obligation for Muslims. By learning the science of recitation with the correct rules, reading the Koran will not make mistakes in both the pronunciation and the meaning of the verses read, so that reading the Koran can be of worship value. From this discussion, we as prospective educators at the MIN/SDN level should start paying attention to the quality of children regarding reading and writing the Koran correctly. This study aims to obtain information about reading and writing skills of the Koran in class V-E MIN 12 Medan Tembung. The method used in this study is to use a qualitative approach because it presents data in the form of words. The type of research used is descriptive research. From the results of the research conducted, it was found that students in class V-E MIN 12 Medan Tembung were able to read the Koran properly and correctly in accordance with the rules of tajwid and makharijul letters and also the writing of the Koran was good and correct. But there are some students who are not at all fluent and proficient in reading the Koran, there are also difficulties in writing the Koran properly and correctly.